Comparison of post-activation potentiating stimuli on jump and sprint performance - Piper, A. D.; Joubert, D. P.; Jones, E. J.; Whitehead, M. T. (International Journal of Exercise Science, 2020)
Post-activation potentiation (PAP) is a phenomenon characterized by improved muscle performance based on the previous contractile activity of the muscle. The purpose of this study was to determine the effect of different potentiating stimuli on jump and sprint performance in 13 resistance trained, college-aged men and women. After determining back squat 1 repetition max, subjects returned for testing on separate days to complete one of four interventions (dynamic resistance, weighted plyometric, isometric, or control) in a randomized order. A standardized warmup was performed, followed by a baseline countermovement jump (CMJ) and 20m sprint. Following warm-up and baseline measurements, subjects performed one of the four experimental conditions. CMJ and 20m sprint measurements were completed again at 20-seconds, 4, 8, 12, 16, and 20-minutes. Results revealed significantly faster 0-20m sprint times (p < .05) at the 4, 8, 12, 16, and 20-minute time points compared to baseline and 20-second time points. Significantly faster 0-20m sprint times (p < .05) were also shown for the squat intervention compared to control at 4-minutes, the plyometric and squat intervention compared to control at 8-minutes, the isometric intervention compared to control at 12 and 16-minutes, and the isometric intervention compared to the squat at 20-minutes. These findings indicate that while all PAP stimuli utilized can be effective at improving sprint performance, specific optimal time points may exist.